Sedimentação como estratégia de separação sólido-líquido e sua influência na remoção biológica de nitrogênio de dejetos suínos - Hollas, Camila Ester (2018)
The intensive animal production generates high volume of effluents, which is potentially damaging to the environment, when improperly managed. One of the production chains known for its high pollutant load is the swine production. An alternative of treatment is to remove ammoniacal nitrogen, which is one of the main pollutant, by nutrient biological removal processes. However, for this to occur properly the solid-liquid separation (SLS) becomes a fundamental step, due to the necessity to reduce total solids and its carbon/nitrogen ratio. Therefore, with the solids removal the discrete particles are removed thereby avoiding overload in subsequent treatment steps. In addition, besides the high nitrogen load, swine manure also presents high organic load when compared to sanitary sewage, which makes possible to use nitrification and denitrification processes to remove nitrogen without the need to add external carbon sources. The modified Ludzack-Ettinger system (MLE) is known as an efficient configuration to use this process for nitrogen and carbon removal from effluents. The objective of this study was to evaluate the influence of SLS process in swine manure for nitrogen removal using a MLE system. For such purpose, a MLE system was carried out with continuous feeding and aeration. The system was fed with effluent from a SLS in tapered decanter, with variable hydraulic retention time (HRT) as a function of volumetric organic matter concentration (volatile solids). The study was conducted in three stages (I, II and III), according to three different hydraulic retention times of the decanter (5, 10, and 30 minutes), pre-determined through tests of sedimentation. The system showed high nitrogen removal efficiency in the three phases under study, 99.6, 99.1%, and 96.5% in each respective phases I, II and III, with high total solids concentration reaching the value of 18.45 g L-1 in the third stage. In addition, the average of carbon removal efficiency was 74.8, 86.3, and 86.3% to phases I, II and III respectively. It was possible verify that the carbon (solids) increase has a detrimental effect on the MLE system, since there is an increase in the oxygen consumption and the sludge volume discarded, leading to an inhibitory effect observed in the kinetic data. It was possible to conclude that the proposed SLS technique used is efficient as a pre-treatment before the nitrogen removal from pig slurry in a MLE system. Moreover, settling times shorter than 30 minutes may cause reduction of nitrification and denitrification efficiency, as well as make the treatment system more expensive.